Karakteristik Gen Sitokrom C Oksidase Sub Unit I (CO1) Lebah Liar Apis cerena (Hymenoptera: apidae) Asal Pulau Hoga Sulawesi Tenggara - Suriana, Suriana; Jamili, Jamili; Parakkasi, Parakkasi (Jurnal Veteriner; Vol 19 No 1 (2018)DO - 10.19087/jveteriner.2018.19.1.116, 2018)
The study was conducted to assess the caracteristic of cytochrome C oxidase subunit I (COI) gene on wild honey bee Apis cerena, and detection of barcode sites from these gene. A total fifteen individual A. cerena were collected from Hoga Island, Southeast Sulawesi. Genomic DNA was extracted from torax, then amplified by PCR method and than sequenced. Sequencing result characterized their nucleotide and amino acid content. The results showed that 595 nucleotides at the 5' end of COI gene of A. cerena very conserved at the most of the sites. Nucleotide dominated by thymine and adenine bases (± 70%). There are 25 barcoding sites for A. cerena. There are two of these sites are diagnostics for A. cerena from of the Hoga Island. From of 595 basepairs nucleotide were prediction encode 198 amino acid, and only eleven percent of the these are varied between species. Amino acid 91th (treonine) and 103th (asparagin) were diagnostics amino acid for A. cerena from Hoga Island, Southeast Sulawesi. Molecular phylogeny reconstructed based on both nucleotide and amino acid sequence placing apis cerena from Hoga Island, Souteast Sulawesi is closely related to Apis cerena from Genbank source.